COVID-19 restrictions and maternal experience and infant feeding - Mohd Shukri, Nurul Husna; Gan, Wan Ying; Zalbahar @ Zabaha, Nurzalinda; Tusimin, Maiza; Mohamad Nasri, Nuruljannah (Lippincott, Williams & Wilkins, 2021)
Background : The Movement Control Order (MCO), also known as the partial lockdown, was introduced in Malaysia in March 2020 to combat the COVID-19 pandemic, changing many public sector protocols and regulations. This may have implications for neonatal and maternity care and services, especially among new mothers. Objective : The aim of this study was to compare the postnatal experiences and feeding practices between mothers who gave birth before MCO (B-MCO) and during MCO (D-MCO). Method: One thousand fifty-one mothers with an infant under 18 months in Malaysia completed an online survey between July 2020 and October 2020. The survey advertisement was disseminated online via various social media platforms. Results: More D-MCO mothers faced a significant effect on the ability to pay rent/mortgage, with their spouses facing a higher impact on employment. D-MCO mothers were more likely to have changed their birth plans, perceived insufficient breastfeeding support, and experienced changes in postnatal services since MCO. In contrast, more B-MCO mothers had stopped breastfeeding during the MCO and started complementary feeding earlier than planned. Many mothers reported feeling down and lonely and having trouble sleeping and a poor appetite. D-MCO mothers had more time to focus on their health, whereas B-MCO mothers spent more time outdoors. Discussion: MCO affected mothers’ livelihood and postnatal experiences, potentially causing emotional distress. Hence, improved breastfeeding support, particularly at birth, is recommended, as is routine mental health screening during the postnatal checkup. Furthermore, because online contact was readily accessible during the pandemic, the efficacy of online breastfeeding support should be evaluated.